Analisis Kebijakan Luar Negeri Amerika Serikat Pada Demokratisasi Irak Melalui Program USAID 2021 - Mahfud, Fanessa Syailirrahmah; Rezasyah, Teuku (Jurnal ICMES, 2023)
Since 2003, the United States has focused its foreign policy on Iraq to democratize and create peace. However, until 2021, Iraq has yet to become a democratic country and remains a conflict-ridden region. In an effort to democratize Iraq, US provides assistance to the country, through the United States Agency for International Development (USAID). The findings of this research indicate that the US government's agenda in Iraq has experienced failures, evident, for example, in the 2021 general elections where Iraq still faced a political crisis and numerous human rights violations. Additionally, corruption and armed conflicts continue to occur in Iraq. It can be concluded that Iraq has not yet become a democratic country. It was found that the reasons behind this situation include human rights abuses and coercion by the United States itself in its efforts to spread liberal democracy.